Co-Morbidity of DSM-IV Personality Disorder in Major Depressive Disorder Among Psychiatric Outpatients in China: A Further Analysis of an Epidemiologic Survey in a Clinical Population - Zheng, Yuchen; Severino, Francesca; Hui, Li; Wu, HaiSu; Wang, Jijun; Zhang, Tianhong (Frontiers in Psychiatry, 2019)
Introduction: It is common that personality disorder (PD) co-occurs with major depressive disorder (MDD). In the current literature, there is a dearth of information on the co-occurrence of PD and MDD among Chinese population. Material and methods: 609 individuals were randomly sampled from outpatients diagnosed as MDD in Shanghai Mental Health Center. Co-morbidity of PDs was assessed using the Personality Diagnostic Questionnaire (PDQ-4+) and eligible subjects were interviewed with the Structured Clinical Interview (SCID-II). The score of PDQ-4+ and the rate of SCID-II PD between subjects diagnosed with MDD and those with anxiety disorders (AD) were compared. Results: 258 outpatients (42.36 %) with MDD were recognized to possess at least one criterion of diagnosis for PD, according to the DSM-IV. The most prevalent PD was depressive PD (14.61 %), followed by avoidant (11.49 %) and borderline (11.49 %) PD. Cluster C PDs (anxious and panic PD) were the most common PD types (12.12 %) when compared to other clusters. Compared to patients with AD, individuals with MDD were significantly more likely to have paranoid PD (6.6 % vs. 3.3 %, p = 0.011), borderline PD (11.5% vs. 3.7 %, p = 0.000), passive-aggressive PD (5.6 % vs. 2.4 %, p = 0.007) and depressive PD (14.6 % vs. 7.8 %, p = 0.000). Discussion: The finding indicates that there’s a high prevalence of PD among patients with MDD. More significant co-morbidity rates of PDs in MDD have been found when compared with AD. Further studies for the longitudinal impact of the PD-MDD co-morbidity are in need.